In-situ tribochemical formation of self-lubricating diamond-like carbon films. (November 2018) - Argibay, N.; Babuska, T.F.; Curry, J.F.; Dugger, M.T.; Lu, P.; Adams, D.P.; Nation, B.L.; Doyle, B.L.; Pham, M.; Pimentel, A.; Mowry, C.; Hinkle, A.R.; et al.
Abstract: Diamond-like carbon (DLC) films were tribochemically formed from ambient hydrocarbons on the surface of a highly stable nanocrystalline Pt-Au alloy. A sliding contact between an alumina sphere and Pt-Au coated steel exhibited friction coefficients as low as μ = 0.01 after dry sliding in environments containing trace (ppb) organics. Ex situ analysis indicated that the change in friction coefficient was due to the formation of amorphous carbon films, and Raman spectroscopy and elastic recoil analysis showed that these films consist of sp 2 /sp 3 amorphous carbon with as much as 20% hydrogen. Transmission electron microscopy indicated these films had thicknesses exceeding 100 nm, and were enhanced by the incorporation of worn Pt-Au nanoparticles. The result was highly wear-resistant, low-friction DLC/Pt-Au nanocomposites. Atomistic simulations of hydrocarbons under shear between rigid Pt slabs using a reactive force field showed stress-induced changes in bonding through chain scission, a likely route towards the formation of these coatings. This novel demonstration of in situ tribochemical formation of self-lubricating films has significant impact potential in a wide range of engineering applications. Graphical abstract: Image